Analisis Faktor-Faktor yang Mempengaruhi Motivasi Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam - Mayzura Mayzura; Khairunnisa Mifta Ababil; Fadilah Ramadhani Br Ginting; Tiara Lisa Br Tarigan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research uses a literature study method to analyze the factors that influence students’ learning motivation in Islamic Religious Education subjects. Learning motivation is a crucial aspect of successful learning processes, especially in religious education, which emphasizes affective and spiritual development. Based on a review of various literature sources, it was found that there are several key factors affecting students’ motivation to learn. These include internal factors such as interest, self-confidence, and learning goals, as well as external factors like the role of teachers, family environment, and learning facilities. In addition, the teaching approach used by the educator significantly influences students’ engagement in Islamic Religious Education learning. The literature also shows that implementing varied and contextual learning methods can significantly enhance students’ motivation. This research is expected to serve as a reference for teachers and education practitioners in designing instructional strategies that effectively improve students’ motivation in learning Islamic Religious Education in a sustainable manner.